Electoral rules and manufacturing legislative supermajority: evidence from Singapore. Issue 3 (3rd July 2018) - Tan, Netina; Grofman, Bernard
ABSTRACT: Electoral authoritarian regimes usually preserve the dominance of the ruling party through electoral fraud, violence and intimidation. This paper focuses on the subtler forms of manipulation that undermine the electoral integrity and democratic outcomes. Specifically, we examine how an unusual electoral rule, involving multimember districts elected through plurality bloc voting for party slates, exaggerates the legislative seat shares of the People's Action Party (PAP) in Singapore. This rule, used also by other electoral authoritarian regimes, facilitates the manipulation of district magnitude and gerrymandering, especially the 'stacking' form, to produce a large disproportionality which distorts the seats–votes linkage. It operates in an undemocratic fashion by precluding the opposition from gaining anything but token seats as long as the PAP remains the plurality-winning party. The importance of this electoral rule and its manipulation has been overlooked in current work that emphasises redistributive strategies or coercion to repress electoral competition.